The development of information control systems for technological purposes - Іevtushenko, V. I.; Sotnik, S. V. (ХНУРЕ, 2026)
The work is devoted to the significance and evolution of information management systems for technological purposes. A review of the transformation of MES systems from monitoring tools to predictive analytics platforms is conducted. The evolution of SCADA system architectures from centralized models to cloud-based and web-oriented solutions is analyzed. Mechanisms of compatibility and integration of PLM and ERP systems within a unified information space of an enterprise are also considered. The research results can be used in the design and modernization of integrated information environments for modern industrial enterprises. Робота присвячена значенню та еволюції інформаційних управляючих систем технологічного призначення. Проведено огляд трансформації MES-систем від засобів моніторингу до платформ прогнозної аналітики. Проаналізовано еволюцію архітектур SCADA-систем від централізованих моделей до хмарних та веб-орієнтованих рішень. Також розглянуто механізми сумісності та інтеграції PLM- та ERP-систем у єдиному інформаційному просторі підприємства. Результати дослідження можуть бути використані при проектуванні та модернізації інтегрованих інформаційних середовищ сучасних промислових підприємств.
Розвиток інформаційних управляючих систем технологічного призначення
Keywords: predictive analytics; industrial automation; PLM; ERP; прогнозна аналітика; промислова автоматика